Intercalibration of benthic foraminiferal and macrofaunal biotic indices: An example from the Norwegian Skagerrak coast (NE North Sea). (January 2019) - Alve, Elisabeth; Hess, Silvia; Bouchet, Vincent M.P.; Dolven, Jane K.; Rygg, Brage
Highlights: The foraminifera-based multimetric Norwegian Quality Index, NQI_f, is proposed. Foraminifera-based indices are intercalibrated with macrofauna-based indices. Foraminifera- and macrofauna-based indices reflect the environment similarly. Foraminifera may assess present and past Ecological Quality Status in coastal waters. Benthic foraminifera are recommended to be accepted as Biological Quality Elements. Abstract: The present study illustrates how benthic macrofauna indices can be adapted to foraminifera through intercalibration of data from common sites. As an example of how benthic foraminifera can fit into governmental monitoring programs, we focus on Norwegian conditions by proposing a new foraminifera-based multimetric index, NQI_f . The index is an adaptation of the Norwegian Quality Index (NQI), which is an internationally intercalibrated macrofauna index. The study is based on published and new data for soft-bottom benthic foraminifera, macro invertebrates, and associated bottom water dissolved oxygen and sediment total organic carbon (TOC). Paired samples of foraminifera and macrofauna were collected at the same stations, at more or less the same time, along the Norwegian Skagerrak coast, NE North Sea. The intercalibration was based on linear regression and the EcoQS class boundary values for the foraminifera indices were derived from boundary values for the macrofauna indices defined by the Norwegian governmental guidelines. The correlations between foraminifera and macrofauna for the multimetric NQI and the diversity indices H′log2 and ES100 were all acceptable for intercalibration (according to the Water Framework Directive's guidelines) but NQI showed the best correlation. Both foraminifera- and macrofauna-indices showed significant correlations with the bottom water dissolved oxygen concentration, and for some indices, with the TOC content in the sediment. Overall, the foraminifera and macrofauna indices reflected the environmental conditions similarly but at the most oxygen depleted stations only foraminifera were present. Based on the present findings and on previous studies which show a potential of fossil foraminifera to define in situ reference conditions, we recommend that foraminifera are accepted as a Biological Quality Element within the WFD.